Position-controlled laser-induced creation of rutile TiO2 nanostructures. (28th May 2019) - Kalb, Julian; Weller, Fabian; Irmler, Lukas; Knittel, Vanessa; Graus, Philipp; Boneberg, Johannes; Schmidt-Mende, Lukas
Abstract: For potential applications of nanostructures, control over their position is important. In this report, we introduce two continuous wave laser-based lithography techniques which allow texturing thin TiO2 films to create a fine rutile TiO2 structure on silicon via spatially confined oxidation or a solid–liquid–solid phase transition, for initial layers, we use titanium and anatase TiO2, respectively. A frequency-doubled Nd:YAG laser at a wavelength of 532 nm is employed for the lithography process and the samples are characterized with scanning electron microscopy. The local orientation of the created rutile crystals is determined by the spatial orientation of hydrothermally grown rutile TiO2 nanorods. Depending on the technique, we obtain either randomly aligned or highly ordered nanorod ensembles. An additional chemically inert SiO2 cover layer suppresses the chemical and electronic surface properties of TiO2 and is removed locally with the laser treatment. Hence, the resulting texture provides a specific topography and crystal structure as well as a high contrast of surface properties on a nanoscale, including the position-controlled growth of TiO2 nanorods.